Aspirational utility and investment behavior - Aristidou, Andreas; Giga, Aleksandar; Lee, Suk; Zapatero, Fernando (Journal of Financial Economics, 2025)
We explore the extent to which aspirations – such as those forged in the course of social interactions – explain ‘puzzling’ behavioral patterns in investment decisions. We motivate an aspirational utility, reminiscent of Friedman and Savage (1948), where social considerations (e.g., status concerns) provide an economic foundation for aspirations. We show this utility can explain a range of observed investor behaviors, such as the demand for both right- and left-skewed assets; aspects of the disposition effect; and patterns in stock-market participation consistent with empirical observations. We corroborate our theoretical findings with two novel laboratory experimental studies, where we observed participants’ preference for skewness in risky lotteries shift as lab-induced aspirations shifted.